Evaluating Usability Of E-Commerce Websites And Systems For End-User Adoption - Safavi, Roshanak (2008)
The objective of the research is to evaluate variables, both technical and human/social, affecting usability of systems from customers' point of view and satisfaction and loyalty of online customers.